2016
DOI: 10.1155/2016/9760538
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic Controller Based Distributed Generation Integration Strategy for Stochastic Performance Improvement

Abstract: In the restructured environment, distributed generation (DG) is considered as a very promising option due to a high initial capital cost of conventional plants, environmental concerns, and power shortage. Apart from the above, distributed generation (DG) has also abilities to improve performance of feeder. Most of the distribution feeders have radial structure, which compel to observe the impact of distributed generations on feeder performance, having different characteristics and composition of time varying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In other words, if the LED being used as a light source somehow has a wavelength that is less than the wavelengths that the LED receiver would 'emit,' [29]. In our educational opportunity, for instance, pairing an amber LED with a red or amber LED enables us to check for photoemission [30]. Furthermore, the yellow LED can be coupled with the ultraviolet, blue, and green LEDs to see if photoemission happens independent of the yellow LED's brightness [31].…”
Section: Methodsmentioning
confidence: 99%
“…In other words, if the LED being used as a light source somehow has a wavelength that is less than the wavelengths that the LED receiver would 'emit,' [29]. In our educational opportunity, for instance, pairing an amber LED with a red or amber LED enables us to check for photoemission [30]. Furthermore, the yellow LED can be coupled with the ultraviolet, blue, and green LEDs to see if photoemission happens independent of the yellow LED's brightness [31].…”
Section: Methodsmentioning
confidence: 99%
“…In this paper a fuzzy expert system as depicted in figure 3 is utilized for optimum location and sizing of single DG unit, which have capacity of DG is 440 KW per phase and operated between 35 to 73 period of metering time interval [11]. It was observed that substation transformer got overloaded during 35 to 71 metering time interval and favorable to solar photovoltaic integration [6].In this expert system, mamdani fuzzy model is used for DG sizing, whereas sugenon fuzzy model utilized for finding location.…”
Section: Distributed Generationmentioning
confidence: 99%
“…These top 15 vulnerable nodes determined by survivability index (SI), a function of voltage stability margin (VSI) and voltage deviation index (VDI) [11].The membership functions associated each crisp input/output variable and fuzzy rules shown for both fuzzy model are shown in figure 4 to 15. …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation